Rugged and accurate quantitation of colchicine in human plasma to support colchicine poisoning monitoring by using turbulent-flow LC–MS/MS analysis. (December 2013) - Bourgogne, Emmanuel; Soichot, Marion; Latour, Colette; Laprévote, Olivier
Background: Colchicine is a common drug used in inflammatory diseases. The narrow therapeutic index requires fast and reliable techniques for its quantitation. An online, automated sample preparation using TurboFlow™ technology combined with triple-stage quadrupole MS detection was applied to identify colchicine in human plasma and follow intoxications.Methodology: Plasma samples (200 µl) were mixed with deuterated colchicine and protein precipitation ZnSO4 solutions. After centrifugation, supernatants were extracted onto a Cyclone P TurboFlow column and eluted onto a narrowbore Hypersil™ GOLD column with a methanol/water gradient. Analytes were monitored in SRM mode (positive electrospray).Results: Total run time was 9.5 min. Calibration curves ranged from 0.342 to 17.1 ng/ml, with significant linearity (R 2 >0.99). Inter- and intra-assay precisions were <16.8% and accuracy was 84.4–110%.Conclusion: This method is suitable for monitoring intoxication in patients undergoing chronic treatment and is routinely applied to toxicological samples.